Perhitungan Kecepatan Sedimentasi Melalui Pendekatan Usle dan Pengukuran Kandungan Tanah dalam Air Sungai yang Masuk ke dalam Waduk Sermo - Bambang Kun Cahyono; Lukman Hakim; Waljiyanto Waljiyanto; Agus Darmawan Adhi (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
Dam is one of the essential man-made buildings which was developed to various beneficialy purposes such as irrigation, fresh water supply, flooding and drying control, and also tourism. Due to those mentioned functions, condition of the dam has to be maintained continuously especially from sedimentation. Sedimentation is being a serious threat for the continuity of dam services. Protecting dam from sedimentation is not only managing dam area, but also we have to care all watershed area, because the sedimentation is caused by erotion on the area. In order to know the rate of the sedimentation within the dam, measurement and prediction must be done. One of methods to predict and measure the sedimentation is by analyzing geospatial data using USLE Approach, and analyzing suspended sediment in river’s water toward to the dam. By those both analysis, rate of sedimentation happened within the dam can be calculated. This paper try to use geospatial (GIS) based analysis to estimate the sedimentation rate using USLE approach within Ngrancah Watershed. The USLE Formula requires four types of maps, they are soil type, slope, land cover, and rain erosivity maps. Each of maps is classified to the specific standards, then will be analized by overlaying to another map. Another method will be used to estimate these dimentation rate is the suspended sediment measurement. This method was determined using sediment transport formula. The data used are samples of river water ing Ngerancah Watershed that was flow toward to the Sermo Dam, and daily volume of inflow water. Those resulted values, then were compared each other. Based on the calculation, sedimentation rate resulted using USLE Approach is 276.100,917 m3 per year or 8,675 mm thickness per year. While the calculation based on the measurement of suspended sediment in river’s water is 270.206,363 m3 per year or 8,490 mm thickness per year. The difference value between the both methods is 5894,555 m3 per year or 0,185 mm thickness per year. Based on the watershed monitoring guidelines published by The Ministry of Forestry of Indoensia, the Sermo Dam sedimentation rate is categorized in poor class, because the sedimentation rate is exceeding 5 mm per year, as the safe limit of dam sedimentation rate.